CAUSES OF BLINDNESS AND VISUAL IMPAIRMENT AMONG STUDENTS IN INTEGRATED SCHOOL FOR THE BLIND IN BIKANER - POONIA, RAUNAQ; MEENA, SAJJAN SINGH; BHARGAVA, POONAM; BHAKHAR, SATA RAM (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The study was undertaken to find out the causes of blindness and visual impairment among students in integrated schools for the blind in Bikaner city of Rajasthan. Methods: A observational study was conducted in the only blind school of Bikaner city. The understudies in the visually impaired school visited were remembered for the review and informed assents from guardians were gotten. Pertinent visual history and essential visual assessments were completed on the understudies of the visually impaired school. Results: A total of 81 students were examined in school of the blind in Bikaner. The main causes of severe visual impairment and blindness in the better eye of students were microphthalmos (25.92%), corneal scar (20.98%), phthisis bulbi (16.04%), retinal dystrophy (8.64%), optic nerve atrophy (8.64%), buphthalmos/glaucoma (6.17%), amblyopia (3.7%), staphyloma (3.7%), cataract (1.23%), anophthalmos (1.23%), aphakia (1.23%), coloboma (1.23%), retinal detachment (1.23%), etc. Of these, 11 (13.58%) students had preventable causes of blindness. Conclusion: It was observed that inherited infections, corneal scar, glaucoma, and waterfall were the conspicuous reasons for visual impairment among the understudies of visually impaired school. Practically, 13.58% of the students had preventable causes, demonstrating the need of genetical directing and centered intercession.